Preventive Teenage Free Sex Behaviour Through Islamic Communication: A Study Based on Islamic Law - Lutfi, M.; Rais, Muhammad Fauzi (Al-I'lam: Jurnal Komunikasi dan Penyiaran Islam, 2025)
Abstrak: Belakangan ini, seks bebas pada remaja menjadi hal yang serius, khususnya di negara kita Indonesia. Banyak faktor yang menyebabkan terjadinya hal ini, seperti pergaulan bebas, teknologi informasi, dan kurangnya perhatian terhadap pendidikan agama serta pemahaman dari hukum Islam pada remaja. Jika kita lengah terhadap situasi ini, maka hal ini akan menghancurkan masa depan remaja kita. Kita harus berupaya keras dan berkesinambungan untuk menangani situasi ini, misalnya mengoptimalkan peran orang tua, pendidik dan penggiat hukum Islam berpengaruh pada tokoh agama dan masyarakat, serta mengfungsionalkan kegiatan keagamaan dan konselin. Abstract: Recently, casual sex among teenagers has become a serious issue, especially in our country, Indonesia. Many factors contribute to this, such as promiscuity, information technology, and a lack of attention to religious education and understanding from Islamic law to teenagers. If we are careless in responding to this situation, it will destroy the future of our youth. We must make strong and continuous efforts to address this situation, for example, by optimizing the roles of parents, educators, and Islamic law activists. We must also influence religious and community leaders, and utilize religious activities and counseling